Nand gate architectures for memory decoder - Jain, Shivkaran; Chatterjee, Arun Kr. (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
This paper presents some nand gate design styles which when used in decoder reduces energy consumption and delay. Basically conventional, nor style nand, source coupled nand is discussed. The three designs conventional, nor style nand, source coupled nand, ranges in area, speed and power. In nor style nand transistors are added in parallel so high fan-in is obtained and logical effort is reduced. In source coupled nand number of transistors are reduced it give speed of operation compared to an inverter. When simulated and compared it is found that nor style nand is 35% faster and 67 % more power efficient than conventional. Source coupled nand is found to be 36% faster and 82% more power efficient than conventional nand gate.